Pengaruh faktor demografi dan nondemografi terhadap fertilitas di Indonesia - Shafira Ramadhani Nugrahaeni; Lilik Sugiharti (Jurnal Kependudukan Indonesia, 2022)
This study aims to analyze the effect of demographic factors (child mortality, age of first marriage, type of contraception) and non-demographic factors (economic factors represented by income; social factors consisting of mother’s education and work status; and cultural factors represented by ethnicity and religion) on fertility in Indonesia. By applying Ordinary Least Square (OLS) method, this study uses cross-sectional data from Indonesia Family Life Survey Wave 5 in 2014. OLS regression results show that demographic factors that influencing fertility in Indonesia are child mortality, age of first marriage, and type of contraception (IUD and tubectomy). Meanwhile, non-demographic factors that have an effect on fertility in Indonesia are income and mother’s education. Moreover, the significant effect of cultural factor on fertility in Indonesia is only shown partially among ethnic groups.